1999 ネン 1 ガツ ニ ジッシシタ グリーンランドカイ バーレンツカイ ニ オケル コウカイ カンソク - 伊藤, 一; イトウ, ハジメ; Ito, Hajime (1999)
P(論文) 国立極地研究所はロシアのクニポビッチ極域漁業海洋研究所との共同研究として北極域で海洋観測を実施した。調査海域はバレンツ海西部とグリーンランド海北東部である。この海域は炭素吸収域, また深層水形成域として知られている。地球規模炭素循環およびその季節変動の把握を主題とし, 国立極地研究所北極圏環境研究センターの国際共同研究事業の一環として計画した。海上調査作業を速報するとともに, 得られた結果の一部を紹介する。 The National Institute of Polar Research (NIPR) carried out an observation cruise in the Arctic in cooperation with the Knipovich Polar Research Institute of Marine Fisheries and Oceanography (PINRO), Russia. The observation area was the western part of the Barents Sea and north-eastern part of the Greenland Sea. The area is considered to be a major carbon sink and also where bottom water is formed. The field work is reported here together with some preliminary results. departmental bulletin paper